Modelling the Product Development performance of Colombian Companies - Herrera-Hernandez, M. C.; Luna, C.; Prada, L.; Berdugo, C.; Al-Ashaab, Ahmed (Cranfield University Press, 2009)
This paper presents the general model of the Product Development Process (PDP) in the Metal mechanics Industry in Barranquilla-Colombia, since this sector contributes significantly to the productivity of this industrial city. This case study counted on a five-company sample. The main goal was to model the current conditions of the PDP according to the Concurrent Engineering philosophy. The companies were selected according to their productive profile, in order to contrast differences regarding the structure of their productive processes, conformation of multidisciplinary teams, integration of different areas, customers and suppliers to the PDP; human resources, information, technology and marketing constraints.
Organised by: Cranfield University
Keywords: Product Process Development; Concurrent Engineering; Multidisciplinary Teams; Human Resources; Information; Technology and Marketing